Euphemism in Lexical Choices: Reuters’ Headlines on Charlie Kirk’s Death - Galaska, Candrika; Maria, Jessicca; Simamora, Debora Anriyani; Rangkuti, Rahmadsyah (Linguistics and ELT Journal, 2025)
This study used Allan and Burridge's theory of euphemism and Entman's framing theory to examine how Reuters' news headlines on Charlie Kirk's death use euphemism language to influence public opinion. Finding the types and purposes of euphemisms and analyzing how these linguistic devices create ideological framing in global media discourse are the primary objectives.  This study examined the linguistic choices that soften or substitute harsh language in fifteen Reuters headlines published between September 11 and September 25, 2025, using a descriptive qualitative methodology. The findings revealed that Reuters employs various forms of euphemism—such as substitution, distortion, and analogy—not only to maintain journalistic neutrality and politeness but also to frame events in ways that influence audience interpretation. Euphemism terms like right-wing, political violence, death penalty, and authorities serve to downplay negativity, legitimize institutional actions, and neutralize ideological tension. The study concludes that euphemism in media is not merely a linguistic device for politeness but also an ideological tool that sustains objectivity, reinforces authority, and subtly guides public discourse within global journalism.